Point Subtraction Aggression Paradigm: Validity of a Brief Schedule of Use - Golomb, Beatrice A.; Cortez-Perez, Myrna; Jaworski, Beth A.; Mednick, Sarnoff; Dimsdale, Joel (Violence and victims, 2007)
The Point Subtraction Aggression Paradigm (PSAP) is a validated behavioral measure of aggression in response to provocation. Canonically, multiple sessions continue until performance asymptotes, requiring significant time. We sought to examine whether use of the PSAP-first-session ("PSAP-FS") had acceptable construct validity for group data, potentially expanding the settings in which the PSAP may be useful. One hundred male and female young adult subjects completed the PSAP-FS and additional behavioral measures of aggression, and provided information related to risk factors. The PSAP-FS correlated significantly with known risk factors of aggression. The PSAP-FS, which measures aggression in the present, correlated well with measures of recent aggression and less strongly with life history of aggression. The PSAP-FS had satisfactory validity properties for use where group-level data are of interest.